Adolescent diabetes induced by multiple parental exposures to cigarette smoke condensate. (10th October 2019) - Wu, Xunwei; Huang, Jun; Dai, Lijuan; Zhou, Jiayi; Huang, Zhaofeng; Yu, Bolan
Highlights: Parental exposure to cigarette smoke causes metabolism abnormality in offspring. Multiple parental exposures significantly increase this long-term disease risk. Offspring with metabolic abnormalities have intestinal microbiota alterations. Abstract: Parental exposure to cigarette smoke is closely related to the development of long-term metabolic diseases in the offspring. However, different exposure times at various developmental stages may cause these effects to vary. In this study, mice were exposed to cigarette smoke condensate (CSC) during the developmental time stages of paternal puberty or/and maternal pregnancy. The results showed that either paternal or maternal exposure to CSC could lead to increased low birth weight (LBW) and fetal growth restriction (FGR) of the offspring, but maternal factors were the leading ones. Moreover, maternal exposure during pregnancy could induce lipid metabolism abnormalities in the adulthood offspring. Most importantly, additional paternal CSC exposure further induced diabetes in adolescent offspring who experienced altered weight gain, blood lipids, and glucose metabolism. A preliminary analysis indicated that the offspring with metabolic abnormalities also had significant changes in their intestinal microbiota. In conclusion, this study showed that parental CSC exposure has an impact on the metabolic properties of the offspring, and multiple parental exposures to adverse factors may significantly increase the risk of long-term metabolic abnormalities.